2010
DOI: 10.1007/s11604-010-0424-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal scanning technique to cover the whole breast using an automated breast volume scanner

Abstract: The four-scans technique for the major segments of the breast is thought to be an operator-independent, feasible method for performing automated breast US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…4 Originally, ABVS was a diagnostic US system developed for breast cancer screening. The scanned data are preserved as three-dimensional (3D) volume data, and the lesions are evaluated using multiplanar reconstruction (MPR) images after scanning.…”
Section: Introductionmentioning
confidence: 99%
“…4 Originally, ABVS was a diagnostic US system developed for breast cancer screening. The scanned data are preserved as three-dimensional (3D) volume data, and the lesions are evaluated using multiplanar reconstruction (MPR) images after scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Less blood flow was observed in epicenter on CDFI. Using CEUS, its enhancement pattern was hyperechoic and quantitative analysis showed that PI of the epicenter was significantly lower than adjacent 16 The most significant difference from previous studies was the perfusion in adjacent regions. A majority of studies reported significant posttraumatic hypoperfusion in adjacent segments of spinal cord.…”
Section: Discussionmentioning
confidence: 57%
“…The Pharmaceutical Affairs Authority in Japan has approved the ABVS as a medical device, and Tozaki et al 7 have proposed a four-scan technique to cover the whole breast with the ABVS. This technique was devised through placing emphasis on fully encompassing even the peripheral regions of the mammary gland and, to this effect, has been being put forward as an optimal scanning method.…”
Section: Discussionmentioning
confidence: 99%
“…The scanning of the four segments of the breast included sequential scans in the upper-outer (C), lower-outer (D), lower-inner (B), and upper-inner (A) regions. 7 For all the scans, the scanning direction was from the periphery of the mammary gland to the nipple. Scanning was stopped after the nipple was scanned completely.…”
Section: Breast Usmentioning
confidence: 99%
See 1 more Smart Citation